2016
DOI: 10.1016/j.cobeha.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding emotion-driven temporal distortions

Abstract: Emotions are powerful drivers of distortions in time perception. Recent work continues to support arousal and attentional mechanisms of emotion-driven temporal distortions. A possible memory-related mechanism and various modulatory factors, such as age, gender, and psychopathology, have also been implicated in such distortions. Beyond the rich behavioral literature on this topic, neurobiological substrates associated with emotion-driven temporal distortions have begun to be identified and represent an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 63 publications
0
47
0
Order By: Relevance
“…Given that senescence is observed in natural populations of animals—affecting their foraging strategies based, in part, on interval timing and the setting of temporal horizons (Bateson, 2003 ; MacDonald et al, 2007 ), the understanding of age-related changes in timing and time perception would appear to have widespread implications for bio-gerontology, emotional regulation, time-based prospective memory and other types of temporal cognition (e.g., Löckenhoff and Carstensen, 2007 ; Löckenhoff, 2011 ; Alexander et al, 2012 ; Nussey et al, 2013 ; Anderson et al, 2014 ; Fingelkurts and Fingelkurts, 2014 ; Matthews and Meck, 2014 , 2016 ; Tucci et al, 2014 ; Vanneste et al, 2015 ; Lake, 2016 ; Lake et al, 2016 ; Mather, 2016 ). By providing a foundation for evaluating brain aging effects on timing and time perception we are now better prepared to evaluate the need for and effectiveness of interventions designed to alleviate age-related declines in temporal cognition (Roberts and Allen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that senescence is observed in natural populations of animals—affecting their foraging strategies based, in part, on interval timing and the setting of temporal horizons (Bateson, 2003 ; MacDonald et al, 2007 ), the understanding of age-related changes in timing and time perception would appear to have widespread implications for bio-gerontology, emotional regulation, time-based prospective memory and other types of temporal cognition (e.g., Löckenhoff and Carstensen, 2007 ; Löckenhoff, 2011 ; Alexander et al, 2012 ; Nussey et al, 2013 ; Anderson et al, 2014 ; Fingelkurts and Fingelkurts, 2014 ; Matthews and Meck, 2014 , 2016 ; Tucci et al, 2014 ; Vanneste et al, 2015 ; Lake, 2016 ; Lake et al, 2016 ; Mather, 2016 ). By providing a foundation for evaluating brain aging effects on timing and time perception we are now better prepared to evaluate the need for and effectiveness of interventions designed to alleviate age-related declines in temporal cognition (Roberts and Allen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the manipulation of time perception can influence the intensity of perceived pain (15), as well as emotional responses (16). If perceived time can also influence glucose levels, the research will provide further evidence of the inextricable relationship between mind and body.…”
mentioning
confidence: 88%
“…Furthermore, many commonly prescribed drugs powerfully modulate dopaminergic signaling. Thus, understanding the precise mechanism of dopaminergic control of emotion and clock speed is of great clinical relevance, as it may help provide insight into symptoms of Parkinson's disease, schizophrenia, and ADHD, as well as help develop and tune current and novel therapies and genetic tests for these and other human diseases including drug abuse, anxiety, and depression (e.g., Bartholomew et al, 2015;Howland, 2012;Lake, 2016;Lake et al, in press;Meck, 2005;Schapira et al, 2006;Thönes & Oberfeld, 2015;Tomasi et al, 2015;Wittmann et al, 2007).…”
Section: Clinical Correlationsmentioning
confidence: 99%